Manajemen Pembelajaran Berbasis Smart Classroom untuk Meningkatkan Hasil Belajar Siswa SMA - Edi Gunarto; Huriyah Huriyah; Didin Nurul Rosidin (IAIN Syekh Nurjati Cirebon, 2023)
Smart Classroom-based learning with various existing models is an innovation that can be carried out by educational institutions to improve the quality of the learning process. For this reason, it is necessary to study the management of learning based on the SMA Smart Classroom so that the learning process is aligned with the learning objectives The purpose of research are to find out how Smart Classroom-based learning management and how Smart Classroom learning management is analyzed at the high school level. The writing of this article was carried out using a qualitative method by collecting data from various sources of literature which the writer obtained from books and journals. One of the findings of this reasearch is that teachers who play a role in Smart Classroom-based learning must have good classroom management skills and pedagogical skills. For this reason, institutions that implement Smart Classroom learning need to prepare various trainings for teachers both in terms of management, technical skills, and pedagogy so as to obtain optimal results in utilizing the Smart Classroom environment.